Marketing Strategy Using Positioning, Differentiation, and Branding to Gain Advantage in the Banana Bread Shop - Sevilla Asysyahidah Al Haq; Mardiyah Hayati; Dwi Ratna Hidayati (Universitas Muhammadiyah Jakarta, 2025)
Banana Bread Shop is one of the small and medium enterprises in Jombang Regency. The increasing number of bakery businesses has intensified market competition, requiring an appropriate marketing strategy. This study aimed to identify Positioning, Differentiation, and Branding (PDB) strategies to build a competitive advantage. The research used a qualitative descriptive method with a case study approach and in-depth interviews. Primary data were collected from purposively selected informants. The results reveal that successful positioning strategies include maintaining product quality, convenient delivery access, clear product information, competitive pricing, and product safety. Differentiation focuses on bread taste and aroma, franchising, and modern equipment. Branding relies on a memorable logo and packaging, affordability, distinctive flavor, and product consistency. Recommendations include adding new flavor variants, improving online responsiveness, creating official social media, and uniforming sales staff to enhance visibility